Pierre Trudeau’s White Paper and the Struggle for Aboriginal Rights in Canada: An Analysis of the Extent to which the White Paper was a Turning Point in the Struggle for Aboriginal Rights and Land Claims in Canada - Kerr, Elisabetta A. (The Great Lakes Journal of Undergraduate History, 2024)
This paper contends that Pierre Trudeau’s 1969 “White Paper” on the status of Aboriginals in Canada was not a major turning point in improving the status of Aboriginals in Canada, but succeeded in inspiring activism and interest in the plight of Canada’s First Nations. The policy attempted to redefine the Canadian government’s relationship with its Aboriginal peoples, expressing the centrality of the government in Aboriginal affairs and reinforcing its obliviousness to the needs of Canada’s First Nations. The White Paper proposed to remove “Indian Status” for Aboriginals, and as a result was vehemently rejected. The effects of the proposed revocation of Status Indians persisted through the social activism and awareness that it inspired. This paper traces the development British- Aboriginal relations following the fall of New France. Diplomacy and treaty-making in the prelude to the White Paper will be considered, along with the changing conception of “Indian Status” throughout Canadian history. Thus, this paper argues that although the White Paper was a necessary step in the realization of the dire condition of Aboriginals in Canada, it did not provoke any lasting government policies that recognized absolute Aboriginal rights and liberties.